Psychological well-being and sociocultural adaptation in college-aged, repatriated, missionary kids - Klemens, Michael J. (Mental health, religion & culture, 2009)
A growing body of literature suggests that children of international missionaries (missionary kids; MKs) struggle with repatriation and have lower levels of well-being than non-MK peers. Unfortunately, many of these reports provide only frequency or bivariate-level data, fail to report the magnitude of differences or problems, and are not theoretically driven. We responded to these needs with a multivariate comparison of 63 MKs and 63 university students (with no expatriation history) from a Christian university. Results indicated significant differences between the MK and university student samples on measures of psychological well-being and sociocultural adaptation. Moreover, a mediated model, with sociocultural adaptation as a mediator between psychological well-being and MK status, was supported. MK supporters, such as recipient universities, mission-sending organisations, and the Christian fraternity Mu Kappa may be able to assist with some of the sociocultural adaptation challenges identified (e.g. understanding the American perspective, interacting with others, understanding humour).